2003 IEEE International Workshop on Workload Characterization (IEEE Cat. No.03EX775)
DOI: 10.1109/phycon.2003.1236871
|View full text |Cite
|
Sign up to set email alerts
|

Stability of delayed feedback controllers for discrete time systems

Abstract: We consider the stability of delayed feedback control (DFC) scheme for multi-dimensional discrete time systems. We first construct a map whose fixed points correspond to the periodic orbits of the uncontrolled system. Then the stability of the DFC is analyzed as the stability of the corresponding equilibrium point of the constructed map. For each periodic orbit, we construct a characteristic polynomial whose Schur stability corresponds to the stability of DFC scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The study of DFC revealed that this scheme has some inherent limitations, that is it cannot stabilize certain type of unstable periodic orbits, see e.g. (Morgül, 2003), (Ushio, 1996), (Nakajima, 1997), (Morgül, 2005a). We note that a recent result presented in (Fiedler et al, 2007), showed clearly that under certain cases, odd number limitation property does not hold for autonomous continuous time systems.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The study of DFC revealed that this scheme has some inherent limitations, that is it cannot stabilize certain type of unstable periodic orbits, see e.g. (Morgül, 2003), (Ushio, 1996), (Nakajima, 1997), (Morgül, 2005a). We note that a recent result presented in (Fiedler et al, 2007), showed clearly that under certain cases, odd number limitation property does not hold for autonomous continuous time systems.…”
Section: Introductionmentioning
confidence: 76%
“…Although the subject is still open and deserves further investigation, we note that the limitation of DFC stated above holds for discrete time case, see e.g. (Ushio, 1996), (Morgül, 2003), (Morgül, 2005a).…”
Section: Introductionmentioning
confidence: 98%
“…It can be shown that Σ T cannot be stabilized with this scheme if [Ushio, 1996;Morgül, 2003a], and a similar condition can be generalized to the case n > 1 [Hino et al, 2002]. A set of necessary and sufficient conditions to guarantee exponential stabilization for n = 1 and n ≥ 1 can be found in [Morgül, 2003a] and [Morgül, 2005a], respectively.…”
Section: Problem Statementmentioning
confidence: 97%
“…This modification, which is also used in [Morgül, 2003a[Morgül, , 2005a[Morgül, , 2005b, does not change the generality of the results. Note that the DPDFC scheme given by (12) and (13) achieves only local stabilization, i.e.…”
Section: A Simple Implementationmentioning
confidence: 99%
See 1 more Smart Citation